Sustainable Finance And Corporate Performance: The Role Of Green Investment, ESG Disclosure, And Capital Structure - Wijaya, Indra (Malaqbi Publisher, 2025)
This study investigates the relationship between sustainable finance and corporate performance by examining the roles of green investment, ESG disclosure, and capital structure. Drawing on data from firms across multiple sectors, the research employs quantitative analysis to explore how sustainability-oriented practices influence financial outcomes. The results demonstrate that green investment has a positive and significant effect on corporate performance, underscoring its role in driving innovation, efficiency, and long-term growth. ESG disclosure is also found to enhance firm value by increasing transparency, strengthening stakeholder confidence, and aligning corporate behavior with environmental and social expectations. Furthermore, the study reveals that capital structure plays a moderating role, where firms that strategically balance debt and equity in alignment with sustainability goals are more resilient and competitive. These findings contribute to the growing body of literature on sustainable finance, highlighting its importance not only as a compliance mechanism but also as a strategic approach to achieving superior corporate performance. The study provides practical implications for corporate managers, investors, and policymakers in promoting sustainability-driven financial strategies.